Strengthening The Character of Pacifism Through History Learning at Madrasah Aliyah in Aceh - Inayatillah, Inayatillah; Yussuf, Ahmad; Kurniawan, Ade; Hasnadi, Hasnadi (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2024)
The study aims to describe and analyze the process of learning history and strengthening pacifism characters in Madrasah Aliyah Aceh with data collection locations carried out in Pidie, Banda Aceh, West Aceh, and East Aceh. The subjects in this study were the head of the Madrasah, the teacher of history subjects and the supervisor of the madrasa. Data collection was conducted through interviews, observations, Focus Group Discussions and document studies. The results showed that the process of learning History at Madrasah Aliyah in Aceh had been carried out with several records of findings. There are still teachers who copy and paste in compiling lesson plans without making modifications. Active involvement of students in the history learning process is still lacking. This can be seen from the passivity of students, teachers rarely invite students to discuss, learning is still dominant in one direction and learning that has not been able to involve students' higher-order thinking skills. History teachers do not analyze evaluation instruments caused by the teacher's lack of understanding in conducting question point analysis. Then, the strengthening of pacifism character through history learning at Madrasah Aliyah in Aceh has not been carried out optimally. This happens because pacifism characters have not become priority characters in schools, pacifism character education-based lesson plans have not been implemented, history teachers have not all made lesson plans as a guideline in carrying out learning, history teachers have different educational backgrounds, teacher pedagogic competence and lack of history teacher development activities.